Correlation Between Blood Glucose and Estradiol Levels in Women in Reproductive Age (Majalah Kedokteran Bandung, 2020)
Type 2 Diabetes mellitus (Type 2 DM) is a metabolic disorder characterized by an increase in blood sugar caused by decreased insulin secretion by pancreatic beta cells and/or impaired insulin function (insulin resistance). This study aimed to determine the specific levels of estradiol hormone in reproductive age women with diabetes mellitus in different age groups. This was an analytical study in  September at Royal Prima Hospital, North Sumatra, Indonesia. Twenty women participated in this study after informed consent and were divided into two age groups: 40–45 years old and 46–50 years old.  Blood samples were collected after 10-12 hours of fasting to assess blood sugar and estradiol hormone levels. Data were then analyzed using the dependent t-test dependent and compared. No significant difference in blood sugar level was found between the two age groups (p-value=0.113, p-value> 0.05) that there were no significant differences in blood sugar levels between the two age groups. The estradiol hormone level in the age group 40-45 years was lower than in the age group 46–50 years, and the difference was significant (p-value =0.000, p-value0.05) sehingga tidak ada perbedaan kadar gula darah yang bermakna antara kedua kelompok tersebut. Kadar hormon estradiol pada kelompok usia 40–45 tahun memiliki kadar estadiol lebih rendah dibanding dengan kelompok usia 46–50 tahun. Tidak terdapat korelasi antara DM tipe 2 dan hormon estradiol yang bermakna pada  penelitian ini.. Simpulam, bahwa usia bukan merupakan faktor penyebab utama peningkatan dan penurunan kadar gula darah dan DM tipe 2 tidak berhubungan dengan hormon estradiol.
Keywords: Estradiol level; hormone; type 2 diabetes mellitus